Strategi Membangun Anak Sehat, Cerdas, dan Bahagia melalui Integrasi Olahraga dalam Pendidikan Anak Usia Dini - Andi Al Muhammad Ardiansyah (FKIP UNSULTRA, 2025)
Early Childhood Education (ECE) is a fundamental phase in establishing the foundation for children's physical, cognitive, social, and emotional development. Integrating sports into ECE learning is a crucial strategy for developing healthy, intelligent, and happy children. Sports activities not only play a role in improving physical fitness but also support the development of gross and fine motor skills, concentration, social skills, and emotional control. This study uses a literature review approach, reviewing various previous research findings related to the application of sports activities in the ECE context. The results indicate that the implementation of structured sports, such as movement games, children's gymnastics, and outdoor activities, has been proven to improve children's coordination, self-confidence, and social interaction. Furthermore, sports contribute to children's happiness through the release of endorphins, which reduce stress and increase learning motivation. The integration of sports combined with an active and playful learning approach provides comprehensive benefits for child development. Therefore, an educational strategy that integrates sports and learning in ECE provides an important foundation for developing a healthy, intelligent, and happy young generation.